Pengembangan Perangkat Pembelajaran Matematika Berbantuan Media Cabri Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas V Sekolah Dasar - Putri Atjo, Syamsuryani Eka (Universitas Negeri Makassar, 2021)
This research aims at developing learning mathematics utilized by Cabri media to improve fifth graders’ ability problem-solving. This research develops learning instruments using Plomp Model. The developed learning instruments are syllabus, lesson plans, teaching materials, students worksheets, and problem solving abilities test. The subjects are students in the fifth grade of State Elementary School 3 of Makassar. The result shows the implementation of learning mathematics utilizing the developed learning instruments is effective. It can be described in more detail that: (1) the characteristics developed learning instruments are revealed valid by validators, (2) the learning completeness classically fulfilled since the result of the experimental group is better than the result of the control group; (3) there is a significant effect in students activities toward the students’ problem-solving abilities, and (4) the students have a positive response to the learning processes that utilize the developed learning instruments.